Evaluation design of the Social Engagement Framework for Addressing the Chronic-disease-challenge (SEFAC): a mindfulness-based intervention to promote the self-management of chronic conditions and a healthy lifestyle - Xuxi Zhang; Siok Swan Tan; Irene Fierloos; Oscar Zanutto; Tamara Alhambra-Borrás; Vanja Vasiljev; Scott Bennett; Tasos Rentoumis; Antonella Buranello; Stefania Macchione; Ellen Rouwet; Amy van Grieken; et al. (BMC, 2019)
Abstract Background The Social Engagement Framework for Addressing the Chronic-disease-challenge (SEFAC) project intends to empower citizens at risk of or with type 2 diabetes (T2DM) and/or cardiovascular disease (CVD) to self-manage their chronic conditions through the SEFAC intervention. The intervention combines the concepts of mindfulness, social engagement and information and communication technology support, in order to reduce the burden of citizens with chronic conditions and to increase the sustainability of the health system in four European countries. Methods A prospective cohort study with a 6-month pre-post design will be conducted in four European countries: Croatia, Italy, the Netherlands and the United Kingdom. A total of 360 community-dwelling citizens ≥50 years of age will be recruited; 200 citizens at risk of T2DM and/or CVD in the next 10 years (50 participants in each country) and 160 citizens with T2DM and/or CVD (40 participants in each country). Effects of the intervention in terms of self-management, healthy lifestyle behavior, social support, stress, depression, sleep and fatigue, adherence to medications and health-related quality of life will be assessed. In addition, a preliminary cost-effectiveness analysis will be performed from a societal and healthcare perspective. Discussion The SEFAC project will further elucidate whether the SEFAC intervention is feasible and (cost-) effective among citizens at risk of and suffering from T2DM and/or CVD in different settings. Trial registration ISRCTN registry number is ISRCTN11248135. Date of registration is 30/08/2018 (retrospectively registered).